Akuntansi Pada Organisasi Sektor Publik - Siti Qiroatin Nasyfa; Bekti Puji Lestari; Danish Priyan Saputra (Jurnal Bisnis Inovatif dan Digital, 2025)
This study aims to examine the implementation of public sector accounting in Indonesia through a literature review approach. The findings indicate that Indonesia has adopted the modified accrual basis as the foundation for public financial reporting, as stipulated in PSAP No. 01 of 2022. However, the transition towards a full accrual system still faces several challenges, including limited understanding of accrual concepts among government personnel, inadequate information technology infrastructure, and bureaucratic culture that remains cash-oriented. This study emphasizes that public sector accounting is not merely a financial recording tool, but also a crucial instrument for promoting transparency, public accountability, and sound public financial governance.